2020
DOI: 10.2147/ceor.s261520
|View full text |Cite
|
Sign up to set email alerts
|

<p>Explaining Socioeconomic Inequality Differences in Catastrophic Health Expenditure Between Urban and Rural Areas of Iran After Health Transformation Plan Implementation</p>

Abstract: Objective Ensuring fair financial contribution is one of the main goals of the Health Transformation Plan (HTP) of Iran. This study aims to estimate socioeconomic inequality differences in catastrophic health expenditure (CHE) between urban and rural areas of Iran after the implementation of the HTP during 2017. Materials and Methods Data from a representative survey of households’ income and xpenditure from the Iran Statistical Center (ISC) were used for the analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Records identified from databases (total n = 5, 849): [114]; [115]; [116]; [117]; [118]; [119]; [120]; [56]; [58]; […”
Section: Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Records identified from databases (total n = 5, 849): [114]; [115]; [116]; [117]; [118]; [119]; [120]; [56]; [58]; […”
Section: Identificationmentioning
confidence: 99%
“…The results from examining the protective effect of different health insurance schemes (Additional file 7) suggest that health insurance in LMICs did not consistently offer a higher degree of FRP. Even though insurance lowered CHE in six studies (in Ghana, Iran, Peru, Thailand and Viet Nam) [34,[52][53][54][55][56], three studies reported higher CHE in India, Iran and Kenya [57][58][59], and another three studies reported not necessarily lower CHE in Colombia, Mexico and Vietnam [60][61][62]. Again, two of these studies showed mixed results: insured households incurred higher CHE but lower impoverishment than the noninsured in India [57], and CHE decreased but impoverishment increased just after launching the Health Transformation Plan in Iran [56].…”
Section: Frp Through Health Insurancementioning
confidence: 99%
“… Original Article/ English 1991 to 2017 Iranian households 48 Abdi,ZH et al 2020 ( 35 ) Undertake a descriptive analysis of changes in health spending associated with implementation of the latest health sector reform in Iran, namely the Health Transformation Plan (HTP). descriptive analytical study WHO method NO Secondary data Original Article/ English 2014 and 2015 Iranian households 49 Kazemi-Karyani, Ali et al 2020 ( 103 ) Estimate socioeconomic inequality differences in CHE between urban and rural areas of Iran after the implementation of the HTP during 2017. Representative survey WHO method, Wagstaff’s normalized concentration index Yes Secondary data Original Article/ English 2017 Iranian households Determinants of exposure to CHE: Socioeconomic status (SES) (+), outpatient services (+), health insurance coverage (-).Sex(Female headed)(+), households with an elderly person(+), with no under-5-year-old children(+), with a family size of 1–2 people (+), living in rural areas (+), with individuals having chronic specific diseases (+), and those who utilize inpatient (+) and outpatient (+), region of residency (+).…”
Section: Search String For Various Databasesmentioning
confidence: 99%
“…Invariably, as financial barriers to health insurance coverage are reduced, problems with physical access to medicines, technology and other necessary services can be effectively addressed by such collaborative partnerships. Moreover, because health insurance funds practically come with patients, the health system’s responsiveness is anticipated to improve due to increasing competition among providers [ 43 ].…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%